2018
DOI: 10.1093/nar/gky305
|View full text |Cite
|
Sign up to set email alerts
|

Introducing structure-switching functionality into small-molecule-binding aptamers via nuclease-directed truncation

Abstract: We report a broadly applicable enzyme digestion strategy for introducing structure-switching functionality into small-molecule-binding aptamers. This procedure is based on our discovery that exonuclease III (Exo III) digestion of aptamers is greatly inhibited by target binding. As a demonstration, we perform Exo III digestion of a pre-folded three-way-junction (TWJ)-structured cocaine-binding aptamer and a stem–loop-structured ATP-binding aptamer. In the absence of target, Exo III catalyzes 3′-to-5′ digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 35 publications
1
75
0
Order By: Relevance
“…To study the binding performance of the A10-excised aptamer, SYBR Green I (SGI) was used for label-free binding assays. [44][45][46][47][48] First, a 50 nM A10-excised aptamer was incubated with 2 mM adenosine ( Fig. 2B).…”
Section: Adenosine Specically Binds To the A10-excised Aptamermentioning
confidence: 99%
“…To study the binding performance of the A10-excised aptamer, SYBR Green I (SGI) was used for label-free binding assays. [44][45][46][47][48] First, a 50 nM A10-excised aptamer was incubated with 2 mM adenosine ( Fig. 2B).…”
Section: Adenosine Specically Binds To the A10-excised Aptamermentioning
confidence: 99%
“…2730 In this work, we found that the binding of small-molecule targets to their respective aptamers can also inhibit exonuclease digestion, and to the best of our knowledge, this is the first work to take advantage of this fact to develop a small-molecule detection assay based on the quantification of aptamer digestion products. We first developed a simple dual-exonuclease-mediated assay that can be generally implemented with unmodified, prefolded aptamers for small-molecule detection.…”
Section: Resultsmentioning
confidence: 92%
“…We further demonstrated the generality of the dual-exonuclease-mediated assay using an ATP-binding aptamer (ATP-33) 30,40 of which the exact structure of its target-binding domain has not been conclusively determined. 4143 ATP-33 is prefolded and forms a hairpin structure with a 7-bp blunt-ended stem that is resistant to Exo I digestion (Figure 6A, Exo I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether aptamer–ligand binding inhibits aptamer digestion by T5 Exo, we used a well-characterized 33-nt DNA aptamer that binds to ATP (ATP-33) ( 34 ) derived from the aptamer isolated by Huizenga and Szostak ( 35 ). We digested ATP-33 with T5 Exo in the absence and presence of ATP, and analyzed the digestion process using polyacrylamide gel electrophoresis (PAGE).…”
Section: Resultsmentioning
confidence: 99%